2019
DOI: 10.31545/intagr/104398
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of regional climate change on barley yield and its geographical variation in South Korea

Abstract: A b s t r a c t. Geospatial variations in barley production due to climate change were evaluated for different geographic regions of South Korea over the next hundred years under the climate change scenarios of representative concentration pathways 4.5 and 8.5. We employed a geospatial crop simulation modelling strategy based on the CERES-barley model in the DSSAT crop model package version 4.6 to simulate grid-based geospatial variation in barley yield. An open field experiment and a temperature gradient fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The Intergovernmental Panel on Climate Change (IPCC) has projected that the global warming trend from 1986–2005 to 2081–2100 will show a temperature increase of 0.3 °C to 1.7 °C [ 18 ]. Therefore, current concerns exist on the impact of global climate change on the production of crops such as barley [ 19 , 20 , 21 ]. Future growing conditions will expose plants to variable and extreme climate change factors, impacting global agriculture, so future research in this area is essential [ 21 ] to take adequate adaptation measures.…”
Section: Introductionmentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change (IPCC) has projected that the global warming trend from 1986–2005 to 2081–2100 will show a temperature increase of 0.3 °C to 1.7 °C [ 18 ]. Therefore, current concerns exist on the impact of global climate change on the production of crops such as barley [ 19 , 20 , 21 ]. Future growing conditions will expose plants to variable and extreme climate change factors, impacting global agriculture, so future research in this area is essential [ 21 ] to take adequate adaptation measures.…”
Section: Introductionmentioning
confidence: 99%
“…It's a highly adaptable cereal grain and ranks fifth among all crops for dry matter production in the world (Thalooth, Bahr, and Tawfik 2012). Barely has wide adaptability to different agro-climatic conditions and different soil properties (Ko et al 2019). Its importance derives from the ability to grow and produce in marginal environments, which are often characterized by drought, low temperature, and salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Although both of the studies of Ko et al (2019) and Cammarano et al (2019) projected incremental changes in temperature in the study regions, they reported different yield patterns. Ko et al (2019) reported that yields would increase in the future while Cammaron et al (2019) predicted that yields would decrease by 8-25% depending on climate projection. Cammaron et al (2019) also reported that barley yields were substantially affected by rainfall and soil moisture content as more yield variation was observed in wet conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Takác and Šiška (2009) used an agroecological model, DAISY, to simulate the yield of spring barley on the Danubian lowland in Slovakia. Other studies used CERES-Barley to simulate the impact of climate change on barley yields in various locations of South Korea (Ko et al, 2019) and in the Mediterranean basin (Cammarano et al, 2019). Although both of the studies of Ko et al (2019) and Cammarano et al (2019) projected incremental changes in temperature in the study regions, they reported different yield patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation